The Students' Creative Thinking Skills Through Science Learning: A Systematic Literature Review - indriyanti, nor (Universitas Sulawesi Barat, 2024)
This study is a Systematic Literature Review (SLR) study. The aim is to conduct a literature study on the relationship between students' creative thinking skills in science learning using the STEM approach. Data collection techniques are carried out by collecting and reviewing articles related to research keywords. A total of 80 articles published in the last 5 years from 2019-2024 from national and international journals from the online databases Google Scholar, Eric, and Garuda. Furthermore, the collected articles were selected according to research criteria and 18 articles were obtained as secondary data. Furthermore, the selected articles became the literature to be analyzed. The findings of this study are 1) Students' creative thinking skills in science learning are very important to be honed and developed as preparation for facing the current global era. 2) STEM-integrated learning has a very positive influence on improving students' creative thinking skills. 3) The implementation of STEM can be integrated with various student-centered learning models, besides STEM can also be implemented with learning media.